Association of Rare Genetic Variants in Opioid Receptors with Tourette Syndrome. (22nd November 2019) - Depienne, Christel; Ciura, Sorana; Trouillard, Oriane; Bouteiller, Delphine; Leitão, Elsa; Nava, Caroline; Keren, Boris; Marie, Yannick; Guegan, Justine; Forlani, Sylvie; Brice, Alexis; Anheim, Mathieu; et al.
Background: Genes involved in Tourette syndrome (TS) remain largely unknown. We aimed to identify genetic factors contributing to TS in a French cohort of 120 individuals using a combination of hypothesis-driven and exome-sequencing approaches. Methods: We first sequenced exons of SLITRK1-6 and HDC in the TS cohort and subsequently sequenced the exome of 12 individuals harboring rare variants in these genes to find additional rare variants contributing to the disorder under the hypothesis of oligogenic inheritance. We further screened three candidate genes ( OPRK1, PCDH10, and NTSR2 ) preferentially expressed in the basal ganglia, and three additional genes involved in neurotensin and opioid signaling ( OPRM1, NTS, and NTSR1 ), and compared variant frequencies in TS patients and 788 matched control individuals. We also investigated the impact of altering the expression of Oprk1 in zebrafish. Results: Thirteen ultrarare missense variants of SLITRK1-6 and HDC were identified in 12 patients. Exome sequencing in these patients revealed rare possibly deleterious variants in 3, 041 genes, 54 of which were preferentially expressed in the basal ganglia. Comparison of variant frequencies altering selected candidate genes in TS and control individuals revealed an excess of potentially disrupting variants in OPRK1, encoding the opioid kappa receptor, in TS patients. Accordingly, we show that downregulation of the Oprk1 orthologue in zebrafish induces a hyperkinetic phenotype in early development. Discussion: These results support a heterogeneous and complex genetic etiology of TS, possibly involving rare variants altering the opioid pathway in some individuals, which could represent a novel therapeutic target in this disorder.